Meningkatkan Profesionalisme Tenaga Keamanan melalui Pelatihan Kesehatan dan Keselamatan Kerja (K3) di Komplek Griya Caraka Bandung - Euis Hernawati; Dian Candra Fatihah; Nuniek Dewi Pramanik; Komarudin; Jusuf Nurdin; Sa'ad Noor; Kasino Martowinangun (LPPM Politeknik Piksi Ganesha, 2026)
Occupational Health and Safety (OHS) training is a crucial component in efforts to increase the capacity and professionalism of security personnel. In high-risk work contexts that require high vigilance, security personnel need to be equipped with a comprehensive understanding of OHS principles to be able to carry out their duties safely, effectively, and responsibly. OHS training not only increases awareness of occupational risks and the implementation of safety procedures, but also strengthens work ethics, discipline, and emergency response skills. Thus, OHS training contributes significantly to developing professional, adaptive security personnel who are able to provide optimal protection to their work environment.